PERSEPSI MAHASISWA TENTANG PENERAPAN PTMT DALAM PEMBELAJARAN BAHASA ARAB MENGGUNAKAN MODEL BLENDED LEARNING - Susanto Susanto; Apri Wardana Ritonga; Ayu Desrani; Suci Ramadhanti Febriani (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2022)
The integration of face-to-face learning offline in classrooms and online using the blended learning model requires the mental readiness of educators and students to achieve the desired learning objectives. This study intends to explore students' perceptions of the application of limited face-to-face learning policies in learning Arabic using a blended learning model. This study adopts a qualitative approach with a case study method at STAI Sabili Bandung, West Java, Indonesia. Research informants totaled 30 people obtained through a questionnaire using Google Form. Data were analyzed through three stages, namely reduction, presentation and verification of data. Finally, the data validation technique uses triangulation of data and data sources. The results of this study indicate that students prefer face-to-face learning using up-to-date learning models and media compared to online learning only. Therefore, creativity and teacher skills are required in designing Arabic learning in accordance with the mandate of global developments. This study recommends further research to analyze the opportunities and challenges of using the blended learning model in learning Arabic. Keywords: Arabic Learning, Blended Learning, PTMT, Learning Technology